Effect of Polyherbal Liver Stimulant (GenoLiv) on Production Performance, Carcass Characteristics, Serum Biochemistry and Immune Response in Commercial Broiler Chickens - Lonkar, Vijaysinh D.; Kadam, Avinash S.; Srivastava, Avinash A.; Chaudhari, Fenil N.; Dhaygude, Vitthal S.; Tumlam, Uma M.; Shinde, Apoorva K. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was aimed to evaluate the efficacy of the polyherbal formulation “GenoLiv” in commercial broiler chicken for growth and productivity. A trial on the VenCobb 430 Y breed of commercial broilers (n=180) was conducted for 35 days. The broilers were divided into two groups, viz., control (basal diet fed) and treatment (basal diet + GenoLiv @ 0.25 kg/MT feed). The parameters like body weight gain, feed consumption, feed conversion ratio (FCR), European production efficiency factor (EPEF), carcass characteristics, organ weights, hematology, serum biochemistry and hemagglutination inhibition (HI) titers were assessed. The results showed enhanced body weight gain by 9.28% and improved FCR by 6.32% in broilers fed with GenoLiv. The EPEF percentage was enhanced by 19.2% compared to the control depicting the improved overall hepatic performance of the broilers. Reduced fat pad percentage by 11.25% illustrated the increased lipid metabolism. The results showed enhanced immune response and improved livability among the GenoLiv-fed birds.
Keywords: Broiler chicken; Carcass characteristics; Hepatostimulant; Polyherbal formulation; Productive performance